PENGEMBANGAN E-COMIC BIOCOM (BIOLOGY COMIC) INTERAKTIF UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA MATERI PEDULI LINGKUNGAN - sinaga, yuliana kristin bernarda; Hulu, Irwan Lihardo; Piliang, Fenny Mustika; Purba, Sumarny Tridelpina (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2025)
This study aims to develop an interactive learning media in the form of an e-comic called Biocom (Biology Comic) to enhance students' scientific literacy on environmental awareness material for Grade X at SMA Swasta Kartika 1-4 Pematangsiantar. The research employed the Research and Development (R&D) method using a modified Borg and Gall development model consisting of ten stages, from identifying potential and problems to product production. The developed media was validated by media and content experts and tested on both small and large student groups. The validation results indicated that the e-comic Biocom is highly valid, with validation scores of 98% (media expert) and 92% (content expert). Student responses were very positive, with an average questionnaire score of 92.5%. Furthermore, the students' pre-test and post-test results showed a significant improvement, with an average N-Gain score of 0.72, categorized as high. Thus, the Biocom e-comic is deemed feasible and effective as a learning media to improve students' scientific literacy on environmental awareness material.